American Girls, Beer, and Glenn Miller : GI Morale in World War II - Cooke, James J. (American military experience series., 2012)
As World War II dawned in Europe, General George C. Marshall, the new Army Chief of Staff, had to acknowledge that American society--and the citizens who would soon become soldiers--had drastically changed in the previous few decades. Almost every home had a radio, movies could talk, and driving in an automobile to the neighborhood soda fountain was part of everyday life. A product of newly created mass consumerism, the soldier of 1940 had expectations of material comfort, even while at war. Historian James J. Cooke presents the first comprehensive look at how Marshall's efforts to cheer soldiers far from home resulted in the enduring morale services that the Army provides still today.